Antiviral and virucidal potential of Origanum vulgare Linn. (oregano) extracts against Bovine alphaherpesvirus 1 (BoHV-1) (Research, Society and Development, 2021)
The search for natural resources with antiviral potential, as an alternative to synthetic drugs, has been growing and, in this sense, oregano presents itself as a potential candidate. However, the antiviral studies with oregano are still poorly explored. BoHV-1 stands out among veterinary pathogens, for its economic impact on cattle production. In this study, the antiviral and virucidal activity of polar extracts of Origanum vulgare was evaluated against BoHV-1. Infusion (INF10), decoction (DEC), and hydroalcoholic (HAE) extracts were tested to cytotoxic and antiviral assays on MDBK cells. Cytotoxic effects were analyzed through MTT assay and the antiviral activity was expressed as a percentage of inhibition (PI). BoHV-1 was incubated with O. vulgare extracts as virucidal assay. Concentrations ≤3.12 mg/ml (INF10) and ≤1.56 mg/ml (DEC/HAE) preserved the cell viability above 60%, and all extracts were safe (>96%) between 0.78 and 0.39 mg/ml. Regarding the antiviral activity, pre-treatment of all extracts highlighted in comparison to the post-treatment. The pre-treatment of infusion at 2 mg/ml highlighted due to the high cell viability (84.69%) and the elimination of the viral load. All extracts inactivated BoHV-1 from 2 hours of incubation (20 mg/ml), showing virucidal activity. These findings may be related to 4-hydroxybenzoic acid as prevalent in all extracts. These findings showed the in vitro antiviral and virucidal activity of oregano polar extracts against BoHV-1 and may be promising for the therapeutic use against herpesviruses infections.